Toxic effects of prolonged endosulfan exposure on some blood parameters in albino rat (Journal of Life and Earth Science, 2011)
Endosulfan is a worldwide used synthetic insecticide that has an important role on management of pests in agriculture. The present work was undertaken to determine the effect of endosulfan on the haematological and haemochemical parameters of albino rats. Rats were feed with 5 mg/kg body weight endosulfan in mixed food stuff for 42 days. The studies were conducted on sexually matured male rats covering five groups of animals with control. Total counts of erythrocytes and haemoglobin were decreased and leucocytes were increased in treated group. Differential counts of leucocytes showed significant increase in basophils and monocytes. The levels of serum glucose, urea, creatinine and bilirubin increased significantly, suggesting that the synthetic insecticide had remarkable toxic effects on the haematological and biochemical parameters in the experimental animals. Key words: Endosulfan; prolonged exposure; haematology; haemochemical parameters; albino rat DOI: 10.3329/jles.v5i0.7346 J. Life Earth Sci., Vol. 5: 29-32, 2010